2016
DOI: 10.1101/059832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of wheat blast in Bangladesh was caused by a South American lineage of Magnaporthe oryzae

Abstract: Background: In February 2016, a new fungal disease was spotted in wheat fields across eight districts in Bangladesh. The epidemic spread to an estimated 15,000 hectares, about 16 % of the cultivated wheat area in Bangladesh, with yield losses reaching up to 100 %. Within weeks of the onset of the epidemic, we performed transcriptome sequencing of symptomatic leaf samples collected directly from Bangladeshi fields. Results: Reinoculation of seedlings with strains isolated from infected wheat grains showed wheat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(145 citation statements)
references
References 33 publications
2
143
0
Order By: Relevance
“…Numerous epidemiological studies of human pathogens have demonstrated environmental or zoonotic origins, but there are fewer studies of bacterial plant pathogens (Almeida and Nunney 2015;Andam et al 2016;Cauchemez et al 2016;Clarke et al 2015;Mather et al 2013;McCann et al 2013;Monteil et al 2016;Quibod et al 2016;Schwartz et al 2015;Shapiro et al 2016;Stukenbrock and Bataillon 2012;Vinatzer et al 2014;Wagner et al 2014;Arango Isaza et al 2016;Depotter et al 2017;Islam et al 2016;Menardo et al 2016). Where ecological and genetic factors restrict pathogens to a small number of plant hosts greater progress has been made, but for facultative pathogens such as P. syringae that colonize multiple hosts and are widely distributed among both plant and nonplant habitats, the environmental reservoirs of disease and factors affecting their evolutionary emergence are difficult to unravel (Singh et al 2011;Monteil et al 2016).…”
Section: Dynamic Genome Evolution Of Psa-3mentioning
confidence: 99%
“…Numerous epidemiological studies of human pathogens have demonstrated environmental or zoonotic origins, but there are fewer studies of bacterial plant pathogens (Almeida and Nunney 2015;Andam et al 2016;Cauchemez et al 2016;Clarke et al 2015;Mather et al 2013;McCann et al 2013;Monteil et al 2016;Quibod et al 2016;Schwartz et al 2015;Shapiro et al 2016;Stukenbrock and Bataillon 2012;Vinatzer et al 2014;Wagner et al 2014;Arango Isaza et al 2016;Depotter et al 2017;Islam et al 2016;Menardo et al 2016). Where ecological and genetic factors restrict pathogens to a small number of plant hosts greater progress has been made, but for facultative pathogens such as P. syringae that colonize multiple hosts and are widely distributed among both plant and nonplant habitats, the environmental reservoirs of disease and factors affecting their evolutionary emergence are difficult to unravel (Singh et al 2011;Monteil et al 2016).…”
Section: Dynamic Genome Evolution Of Psa-3mentioning
confidence: 99%
“…Known examples are the necrotrophic fungi Magnaporthe oryzae, Fusarium graminearum and Ramularia collo-cygni, which all are more virulent in hosts with an mlo background (Jarosch et al, 1999;Jansen et al, 2005;McGrann et al, 2014). This increased susceptibility may be particularly relevant in wheat, in which blast disease caused by Magnaporthe oryzae pathotype Triticum is a critical emerging pathogen (Islam et al, 2016).…”
Section: Intervention By Targeting Recessive Traits/susceptibilitmentioning
confidence: 99%
“…Crop breeding can produce resistance to individual diseases, but it is challenging to select for genetic resistance against multiple diseases simultaneously while maintaining the strong performance traits of elite varieties. For example, wheat blast is an emerging disease that will require wheat breeders to select for blast resistance while maintaining resistance against stem rust (Islam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat blast was first detected on wheat in the 1980s in Brazil (Igarashi et al, 1986), from where it spread to Bolivia in 1996 and Argentina in 2007 (Ceresini et al, 2018). Now well established in South America, it is thought that seedborne inoculum on wheat grain imports from Brazil entered Southeast Asia in 2016, causing severe outbreaks particularly in Bangladesh (Islam et al, 2016; Fig. 1).…”
Section: Mutationmentioning
confidence: 99%